1993
DOI: 10.1172/jci116666
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lovastatin and dietary cholesterol on sterol homeostasis in healthy human subjects.

Abstract: We measured biliary and fecal sterol outputs in 12 human subjects on a metabolic ward in four randomly allocated, [6][7] Judging from these data, the primary action of lovastatin is to lower cholesterol synthesis and systemic cholesterol input, the main compensatory response being reduced biliary cholesterol secretion. Conversely, increased dietary cholesterol appears to increase systemic cholesterol input, the major compensatory response being increased bile acid synthesis. There appears to be no interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
19
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 42 publications
6
19
0
Order By: Relevance
“…In small-scale cholesterol balance studies, Miettinen et al (7)(8)(9) have documented that statins markedly lower cholesterol synthesis and bile acid production, but also significantly increase fractional intestinal cholesterol absorption. Duane (10) reported similar observations. Miettinen, Strandberg, and Gylling (11) have also reported in a subset of CHD patients participating in the Scandinavian Simvastatin Survival Study (4S) that those in the highest quartile of the cholestanol/C ratio (indicative of high cholesterol absorption), while on simvastatin had no reduction in CHD events as compared with the placebo-treated group, with the converse also being the case.…”
supporting
confidence: 54%
“…In small-scale cholesterol balance studies, Miettinen et al (7)(8)(9) have documented that statins markedly lower cholesterol synthesis and bile acid production, but also significantly increase fractional intestinal cholesterol absorption. Duane (10) reported similar observations. Miettinen, Strandberg, and Gylling (11) have also reported in a subset of CHD patients participating in the Scandinavian Simvastatin Survival Study (4S) that those in the highest quartile of the cholestanol/C ratio (indicative of high cholesterol absorption), while on simvastatin had no reduction in CHD events as compared with the placebo-treated group, with the converse also being the case.…”
supporting
confidence: 54%
“…We and others have documented that alterations in specifi c plasma markers of cholesterol absorption, namely, campesterol and ␤ -sitosterol, can affect LDL-C lowering response to statins (17)(18)(19)(20). Moreover, it has been reported that a subset of patients placed on simvastatin in the Scandinavian Simvastatin Survival Study showed no benefi t from therapy compared with placebo if they had elevated baseline levels of markers of cholesterol absorption, including cholestanol ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Direct measurement of the latter has failed to show consistent effects of other statins. 7,13,14 However, a decrease in biliary cholesterol secretion could also lead to an increase in cholesterol absorption, as shown in mice 15 and in dietary studies in humans. 16 Low cholesterol absorption efficiency in obesity may be because of an increased biliary cholesterol pool that competes with dietary cholesterol and noncholesterol sterols for intestinal absorption.…”
Section: Discussionmentioning
confidence: 99%